Teaching quantitative methods : getting the basics right - Payne, Geoff, 1944-; Williams, Malcolm, 1953- (Online access: SAGE SAGE Research Methods Core., 2011)
A clear, innovative text from world experts, this book clearly lays out the problems, strategies and resources associated with the teaching of quantitative methods in modern universities. It is a pragmatic approach which will be of interest to any academic teaching 'numbers' to their students.